The self-efficacy among non-English lecturers in using English as an academic language - Setya Putri Rahayu (Universitas Merdeka Malang, 2021)
The implementation of an English atmosphere will bring abundant impact for all university entities to create a supportive environment in increasing their English competencies. The study aims at investigating the level of self-efficacy among non-English lecturers to use English in any academic setting. The study applied a mixed-method study which formulated a descriptive quantitative analysis and phenomenological approach as a qualitative analysis. The respondents were 19 non-English lecturers of the Physiotherapy program in Universitas ‘Aisyiyah Yogyakarta taken by total sampling; questionnaires were used to collect data quantitatively, and a structured interview was also applied to take qualitative data. The study shows that 50% of lecturers have a moderate rate of self-efficacy in describing their mastery experience although they have a high rate in determining their somatic and emotional states in judging their capability. In addition, vicarious experience does not become a strong predictor in increasing self-efficacy among lecturers. However, rigid policy from the university is the most significant factor in supporting lecturers to use English in academic settings.DOI: 10.26905/enjourme.v6i1.5940